2014
DOI: 10.1016/j.biopsych.2013.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in Brain 5-HT1B Receptor Availability in Primarily Cocaine-Dependent Humans

Abstract: Background Preclinical evidence implicates the 5-HT1B receptor in cocaine’s effects. This study explores 5-HT1B in humans by examining receptor availability in vivo with primary cocaine-dependent (CD) subjects using positron emission tomography (PET). Methods Fourteen medically healthy CD subjects (mean age=41±6 yrs) were compared to 14 age-matched healthy control subjects (41±8 yrs) with no past or current history of cocaine or other illicit substance abuse. Participants received an MRI and then a PET scan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 47 publications
1
33
0
1
Order By: Relevance
“…Slopes were estimated within each region post-hoc and decline per decade was calculated as a percent of the fitted value at age 20. Within-subject correlations were accounted for by fitting three variance-covariance structures to the data (unstructured, compound symmetry, and heterogeneous compound symmetry) and then selecting the best-fitting structure according to the Bayesian Information Criterion (BIC) (Matuskey et al, 2014a; Matuskey et al, 2012). All tests were two-tailed and adjusted for multiple comparisons using the Bonferroni adjustment.…”
Section: Methodsmentioning
confidence: 99%
“…Slopes were estimated within each region post-hoc and decline per decade was calculated as a percent of the fitted value at age 20. Within-subject correlations were accounted for by fitting three variance-covariance structures to the data (unstructured, compound symmetry, and heterogeneous compound symmetry) and then selecting the best-fitting structure according to the Bayesian Information Criterion (BIC) (Matuskey et al, 2014a; Matuskey et al, 2012). All tests were two-tailed and adjusted for multiple comparisons using the Bonferroni adjustment.…”
Section: Methodsmentioning
confidence: 99%
“…PET imaging using 11 C-P943 was performed as described in recent studies from our center (72, 78, 83). The antecubital vein was cannulated for radiotracer delivery.…”
Section: Methodsmentioning
confidence: 99%
“…Positron emission tomography (PET) studies in monkeys showed increased 5-HTT availability in frontal areas after chronic cocaine administration, whereas PET studies in humans revealed that chronic use is associated with reduced 5-HT 1B receptor binding in the PFC (Gould et al, 2011;Matuskey et al, 2013). In addition, studies in rats demonstrated that the TPH2 activity in the raphe nucleus increases after chronic cocaine administration (Vrana et al, 1993).…”
Section: Introductionmentioning
confidence: 99%